John McAuley Palmer papers - Palmer, John McAuley, 1870-1955.; Holley, I. B. (Irving Brinton), 1919-
Correspondence, writings including drafts of Palmer's unpublished memoirs, notes, research material, subject files, biographical material, printed matter, and other papers relating to Palmer's career in the U.S. Army. Documents his service as assistant chief of staff and aide-de-camp to John J. Pershing and as advocate of contemporary military reform based on universal military training (draft) and the citizen soldier. Also documents his work as an author in the field of military history. Includes correspondence and material assembled by Palmer's biographer, I.B. Holley, for his book General John M. Palmer, Citizen Soldiers, and the Army of a Democracy (1982). Family correspondents include Holley's wife, Maude Laning Palmer; his daughter, Mary Palmer Rockwell, and her husband, George H. Rockwell; and Palmer's grandson, John Palmer Chandler. Other correspondents include George C. Marshall and John J. Pershing.
U.S. Army officer and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chandler, John Palmer -- Correspondence; Marshall, George C. -- 1880-1959 -- Correspondence; Palmer, Maude Laning -- Correspondence; Pershing, John J. -- 1860-1948 -- Correspondence; Rockwell, George H. -- Correspondence; Rockwell, Mary Palmer -- Correspondence; United States. -- Army -- Officers; Draft; Military history; Military reform; Army officers; Authors